Salmonellosis in layer chickens: pathological features and isolation of bacteria from ovaries and inner content of laid eggs (Journal of the Bangladesh Agricultural University, 2012)
We isolated and identified Salmonella organisms from ovaries of dead layer birds and from inner content of laid eggs of different poultry farms. The thirty eight ovarian swabs for bacteriology, visceral organs (liver, lung, spleen, egg follicles and intestine) of 38 dead birds for pathological study from 15 layer farms and 45 laid eggs (5 eggs/farm) from reported 9 Salmonella infected farms constituted samples of the study. Samples were subjected to isolation and identification of the causal agent followed by gross and histopathological study of the affected visceral organs. Seventeen of 38 ovarian swabs (44.7%) were Salmonella positive. The percentage of Salmonella Gallinarum, Salmonella Pullorum and paratyphoid causing Salmonella were 70.6%, 17.6% & 11.8%, respectively. About 53% livers of Salmonella affected birds were enlarged, congested, friable and bronze coloured with white necrotic foci. About 59% egg follicles were congested, hemorrhagic, discoloured with stalk formation and 70.6% intestines showed hemorrhagic to catarrhal enteritis. At histopathology, 76.5% livers were congested with formation of multifocal nodules and 82.4% egg follicles were congested with huge leukocytic infiltration. Infiltration of heterophils in intestinal mucosa was found in 47.1% cases. Four Salmonella isolates were found from 9 laid egg samples (5 eggs content comprised as 1 sample) and isolation rate was 44.4% reporting transovarian transmission in poultry Salmonellosis.   DOI: http://dx.doi.org/10.3329/jbau.v10i1.12095   J. Bangladesh Agril. Univ. 10(1): 6167, 2012